Digital accounting based on SAK-ETAP: financial reporting quality as a moderating variable - Evi Juita Wailan' An; Sonya Enda Natasha S Pandia (Jurnal Akademi Akuntansi)
Purpose: This study aims to determine whether the role of information technology and credit quantity influences the presentation of quality financial statements, with the understanding of SAK-ETAP as a moderating variable in creative businesses in Medan City.